Comparison of plasma- and saliva-derived exosomal miRNA profiles reveals diagnostic potential in head and neck cancer - Hofmann, Linda; Abou Kors, Tsima; Ezić, Jasmin; Niesler, Beate; Röth, Ralph; Ludwig, Sonja; Laban, Simon; Schuler, Patrick J.; Hoffmann, Thomas K.; Brunner, Cornelia; Medyany, Valentin; Theodoraki, Marie-Nicole (Frontiers in Cell and Developmental Biology, 2022)
Background: Head and neck squamous cell carcinomas (HNSCC) lack tumor-specific biomarkers. Exosomes from HNSCC patients carry immunomodulatory molecules, and correlate with clinical parameters. We compared miRNA profiles of plasma- and saliva-derived exosomes to reveal liquid biomarker candidates for HNSCC. Methods: Exosomes were isolated by differential ultracentrifugation from corresponding plasma and saliva samples from 11 HNSCC patients and 5 healthy donors (HD). Exosomal miRNA profiles, as determined by nCounter® SPRINT technology, were analyzed regarding their diagnostic and prognostic potential, correlated to clinical data and integrated into network analysis. Results: 119 miRNAs overlapped between plasma- and saliva-derived exosomes of HNSCC patients, from which 29 tumor-exclusive miRNAs, associated with TP53, TGFB1, PRDM1, FOXO1 and CDH1 signaling, were selected. By intra-correlation of tumor-exclusive miRNAs from plasma and saliva, top 10 miRNA candidates with the strongest correlation emerged as diagnostic panels to discriminate cancer and healthy as well as potentially prognostic panels for disease-free survival (DFS). Further, exosomal miRNAs were differentially represented in human papillomavirus (HPV) positive and negative as well as low and high stage disease. Conclusions: A plasma- and a saliva-derived panel of tumor-exclusive exosomal miRNAs hold great potential as liquid biopsy for discrimination between cancer and healthy as well as HPV status and disease stage. Exosomal miRNAs from both biofluids represent a promising tool for future biomarker studies, emphasizing the possibility to substitute plasma by less-invasive saliva collection.